Response - Sayers, Ian; Portelli, Michael A.; Siedlinski, Mateusz (Federation of American Society of Experimental Biology, 2015)
We thank Dr. Rasmussen and colleagues for their comments on our work outlined in “Genome-wide protein QTL mapping identifies human plasma kallikrein as a post-translational regulator of serum uPAR levels” (FASEB J. 28, 923–934) and the opportunity to respond to key points.